Sustainability to oneself to act - Sofian, Fatimah Noor Rashidah Mohd (Kuliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
This chapter is a reflection of what is the purpose of us being here in this world. Everyone has a duty and responsibility given by Allah to manage this world according to His direction and law. A role that was given to me as a lecturer, a wife, a mother, a daughter, the eldest in the family and handling with people surrounds, sometimes troubles me to sustain patience in facing the challenges. One of the ways to maintain patience is to talk to Allah. This chapter reflects my duty, and it is hoped that the written chapter reflects the readers with their situation to sustain oneself act